Somatic Embryogenesis and Plant Regeneration from the Apical Meristem of Wrukwona Napiergrass (Pennisetum purpureum) Treated with Thidiozuron and Cupric Sulfate - N. Umami; A. N. Respati; M. M. Rahman; K. Umpuch; T. Gondo (Tropical Animal Science Journal, 2022)
This study focused on the effectiveness of somatic embryogenesis and regenerated plant in Wrukwona napiergrass. Previously, we studied in vitro propagation of 4 cultivars of napiergrass (Pennisetum purpureum) and showed that only 3.3% of Wrukwona cultivar formed embryogenic callus on day 30 and 21.7% on day 60 of incubation. To improve callus formation performance, it is necessary to develop a special propagation method for Wrukwona cultivar in terms of various growth regulators and additional compounds. This study used several rates of 2.4-dichlorophenoxyacetic acid (2.4-D), benzyl amino purine (BAP), and thidiozuron (TDZ). The result showed that the use of medium Murashige & Skoog (MS) with 2.4-D and BAP at a high ratio of 2.4-D, and TDZ 2 µM formed 78.6% embryogenic callus on day 60th and no albino was found in the regenerated plant. The best combination of growth promotor for embryogenic callus formation was 3 mg L-1 2.4-D, 0.5 mg L-1 BAP, and 2 µM TDZ. Callus proliferation with MS media added with 3 mg L-1 2.4-D, 0.5 mg L-1 BAP, 2 µM TDZ, and 5 µM CuSO4 gave the best proliferation results, with regeneration reaching 65%. All regenerants successfully grew in soil. It can be concluded that somatic embryogenesis of P. purpureum cv. Wrukwona can be produced from MS culture medium using 2 mg L-1 2.4-D, 0.5 mg L-1 BAP, and 2 µM TDZ. Effective multiplication was carried out by adding 5 µM CuSO4 to the same medium as the embryogenic callus formation, and effective regeneration was carried out with MS media containing 2 mg L-1 BAP.